Antimicrobial resistance of uropathogens in older adults - Bravo Osorio, Ivana Patricia; Chero Vargas, Jackeline Del Rosario; Apolaya Segura, Moises (Revista Cubana de Medicina, 2021)
Introduction: At present, antimicrobial resistance has been declared by the World Health Organization as a public health problem. Objective: To determine the antimicrobial resistance profile of uropathogens in older adults. Methods: Cross-sectional descriptive study of 567 positive urine cultures from older adults treated during 2017 in a private clinic in Lima, Peru. Univariate analysis was performed by frequency distribution, mean and standard deviation. The association between ESBL blee production with respect to epidemiological characteristics and type of care is estimated using Chi square with a significance level of 0.05. Results: The average age of the population was 74.1 years (SD: 10.7). 71.8% of the positive urine cultures were from female sex. The main uropathogens isolated at all levels of care were E. coli, E. coli ESBL and K. pneumoniae ESBL. E. coli showed 69.3% resistance to ampicillin; and E. coli ESBL had 100% resistance to ampicillin, ceftriaxone, and ceftazidime. 62% of ESBL microorganisms were found in outpatient care. There was a statistically significant association between ESBL-producing agents and gender (p = 0.004), but not with regard to type of care (p = 0.144) or age subgroups (p = 0.669). Conclusions: Antimicrobial resistance is highly prevalent in older adults. The female sex was the most affected and the most frequent uropathogen was E. coli, highly resistant to ampicillin and greater sensitivity to nitrofurantoin. High percentage of ESBL-producing agents was determined in outpatient care. Keywords: antimicrobial resistance; Elderly; uropathogens.